Motivations for active commuting: a qualitative investigation of the period of home or work relocation. - Jones, C; Ogilvie, D (2012)
BACKGROUND: Promoting walking or cycling to work (active commuting) could help to increase population physical activity levels. According to the habit discontinuity and residential self-selection hypotheses, moving home or workplace is a period when people (re)assess, and may be more likely to change, their travel behavior. Research in this area is dominated by the use of quantitative research methods, but qualitative approaches can provide in-depth insight into the experiences and processes of travel behavior change. This qualitative study aimed to explore experiences and motivations regarding travel behavior around the period of relocation, in an effort to understand how active commuting might be promoted more effectively. METHODS: Participants were recruited from the Commuting and Health in Cambridge study cohort in the UK. Commuters who had moved home, workplace or both between 2009 and 2010 were identified, and a purposive sample was invited to participate in semi-structured interviews regarding their experiences of, and travel behavior before and after, relocating. A grounded theory approach was taken to analysis. RESULTS: Twenty-six commuters participated. Participants were motivated by convenience, speed, cost and reliability when selecting modes of travel for commuting. Physical activity was not a primary motivation, but incidental increases in physical activity were described and valued in association with active commuting, the use of public transport and the use of park-and-ride facilities. CONCLUSIONS: Emphasizing and improving the relative convenience, cost, speed and reliability of active commuting may be a more promising approach to promoting its uptake than emphasizing the health benefits, at least around the time of relocation. Providing good quality public transport and free car parking within walking or cycling distance of major employment sites may encourage the inclusion of active travel in the journey to work, particularly for people who live too far from work to walk or cycle the entire journey. Contrary to a straightforward interpretation of the self-selection hypothesis, people do not necessarily decide how they prefer to travel, relocate, and then travel in their expected way; rather, there is constant negotiation, reassessment and adjustment of travel behavior following relocation which may offer an extended window of opportunity for travel behavior change.